The Phenomenon of Integration of Religious Practices as an Auxiliary Tool in Contemporary Medicine: Ukrainian Hospital Chapels in Modern Times - Ovchar, Mariia (Occasional papers on religion in Eastern Europe, 2022)
The relevance of the research topic is ensured by the wide integration of such religious practices as an aid in contemporary medicine. The article describes the activities of more than 15 currently operating famous hospital chapels. The histories behind the foundation of each of them are analyzed, and the facts of public participation and the leadership of hospitals in the establishment of chapels at medical institutions are given. Special attention is paid to the characteristics of the psychological support component as an auxiliary factor along with the main course of treatment. For clarity of the descriptive part, the study presents nine drawings, emphasizing the diversity and uniqueness of each of the described religious objects. It has been established that chapels at hospitals, in addition to their function as psychological support, also serve as support for spiritual orientation, as well as an additional area for the direct expansion of religious influence in society. At the same time, it is believed that the peculiarity of this kind of integration of religious practices into medical rehabilitation is that the spiritual component of treatment, even at the placebo level, can contribute to the patient's recovery process. In the course of the study, insufficient public coverage of comprehensive information on the functioning of hospital chapels was revealed, and it was also found that Ukrainian and foreign scientists did not study the issue of hospital chapels in the latest relevant publications.